2022
DOI: 10.3389/fcell.2022.886381
|View full text |Cite
|
Sign up to set email alerts
|

A Journey on Extracellular Vesicles for Matrix Metalloproteinases: A Mechanistic Perspective

Abstract: Matrix metalloproteinases (MMPs) are key players in matrix remodeling and their function has been particularly investigated in cancer biology. Indeed, through extracellular matrix (ECM) degradation and shedding of diverse cell surface macromolecules, they are implicated in different steps of tumor development, from local expansion by growth to tissue invasion and metastasis. Interestingly, MMPs are also components of extracellular vesicles (EVs). EVs are membrane-limited organelles that cells release in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Extracellular vesicles are known to contain proteases that are involved in proteolytic degradation of the extracellular matrix. Membrane type 1-matrix metalloproteinase (MT1-MMP) has been found as bioactive cargo in several classes of EVs [23,24]. Substrate targets of MT1-MMP include aggrecan, collagen types I, II, and III, fibronectin, gelatin, laminin-1 and -5, and vitronectin [24,25].…”
Section: Ev Cargo Results In Proteolytic Degradation Of the Ecmmentioning
confidence: 99%
“…Extracellular vesicles are known to contain proteases that are involved in proteolytic degradation of the extracellular matrix. Membrane type 1-matrix metalloproteinase (MT1-MMP) has been found as bioactive cargo in several classes of EVs [23,24]. Substrate targets of MT1-MMP include aggrecan, collagen types I, II, and III, fibronectin, gelatin, laminin-1 and -5, and vitronectin [24,25].…”
Section: Ev Cargo Results In Proteolytic Degradation Of the Ecmmentioning
confidence: 99%
“…A growing number of studies have also detected metalloproteases and integrins in EVs. 58 , 59 , 60 , 61 , 62 , 63 Metalloproteases are thought to contribute to EV biogenesis, modification, and EV uptake by recipient cells through the remodeling of the extracellular matrix (ECM) and the modification of EV and cell surface receptors. 62 , 63 Furthermore, EV-bound integrins are involved in adhesion to the ECM and EV uptake by recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“… 58 , 59 , 60 , 61 , 62 , 63 Metalloproteases are thought to contribute to EV biogenesis, modification, and EV uptake by recipient cells through the remodeling of the extracellular matrix (ECM) and the modification of EV and cell surface receptors. 62 , 63 Furthermore, EV-bound integrins are involved in adhesion to the ECM and EV uptake by recipient cells. 60 , 61 While studies have shown these proteins’ involvement in EV biogenesis, migration through the ECM, and the homing of EVs to specific cell types in disease states such as cancer and kidney disease, these mechanisms and/or resulting biological consequences in the airway are still relatively unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The process of metastasis involves the separation of malignant cells from the primary tumor, local invasion, angiogenesis, and the spread in the circulatory or lymphatic systems, through which they can transfer to distant organs [6]. When cancer spreads, the tissue matrix changes, creating an environment that fosters tumor development, migration, invasion, angiogenesis, and immune suppression [7,8]. MMPs, commonly referred to as matrix metalloproteinase, are present in the extracellular environment of cells and can degrade both matrix and non-matrix proteins.…”
Section: Introductionmentioning
confidence: 99%